ELECTRON MICROSCOPIC STUDIES OF MITOSIS IN AMEBAE : I. Amoeba proteus - Roth, L. E. (The Rockefeller University Press, 1960)
Individual organisms of Amoeba proteus have been fixed in buffered osmium tetroxide in either 0.9 per cent NaCl or 0.01 per cent CaCl(2), sectioned, and studied in the electron microscope in interphase and in several stages of mitosis. The helices typical of interphase nuclei do not coexist with condensed chromatin and thus either represent a DNA configuration unique to interphase or are not DNA at all. The membranes of the complex nuclear envelope are present in all stages observed but are discontinuous in metaphase. The inner, thick, honeycomb layer of the nuclear envelope disappears during prophase, reappearing after telophase when nuclear reconstruction is in progress. Nucleoli decrease in size and number during prophase and re-form during telophase in association with the chromatin network. In the early reconstruction nucleus, the nucleolar material forms into thin, sheet-like configurations which are closely associated with small amounts of chromatin and are closely applied to the inner, partially formed layer of the nuclear envelope. It is proposed that nucleolar material is implicated in the formation of the inner layer of the envelope and that there is a configuration of nucleolar material peculiar to this time. The plasmalemma is partially denuded of its fringe-like material during division.